Effect of product completeness and price on consumer purchasing decision in smes market medan - Harahap, Dedy Ansari; Amanah, Dita; Agustini, Fauzia (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2018)
The aim of this study was to analyze the effect of the product and the price of the purchase decisions of consumers SME market case on Pajak USU (Pajus) Medan. This research uses quantitative approach with explanatory research type. The sample technique used is non probability sampling, the number of samples are 96 respondents selected at random and data collection techniques used are questionnaires that measurement using Likert scale and statistical analysis with multiple linear regression method. The results showed that product completeness partially has no positive and significant effect on consumer purchase decision and price partially have a positive and significant impact on consumer purchase decision. Whereas product completeness and price simultaneously influencing consumer purchase decision in Pajus Medan. The findings confirm that consumers' choice of coming to that place is to buy a product at a cheap price not because of the availability of a more complete product.